2014
DOI: 10.1186/1477-7525-12-23
|View full text |Cite
|
Sign up to set email alerts
|

Measurement equivalence and feasibility of the EORTC QLQ-PR25: paper-and-pencil versus touch-screen administration

Abstract: ObjectiveWe assessed the measurement equivalence and feasibility of the paper-and-pencil and touch-screen modes of administration of the Taiwan Chinese version of the EORTC QLQ-PR25, a commonly used questionnaire to evaluate the health-related quality of life (HRQOL) in patients with prostate cancer in Taiwan.MethodsA cross-over design study was conducted in 99 prostate cancer patients at an urology outpatient clinic. Descriptive exact and global agreement percentages, intraclass correlation, and equivalence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
2
13
1
Order By: Relevance
“…Confirming our findings, Chang et al [ 15 ] also concluded that age and previous computer experience did not explain acceptance of an electronic platform. Pouwer et al [ 22 ] also found that e-PROs were very easy for research participants to use even if they had little computer experience.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Confirming our findings, Chang et al [ 15 ] also concluded that age and previous computer experience did not explain acceptance of an electronic platform. Pouwer et al [ 22 ] also found that e-PROs were very easy for research participants to use even if they had little computer experience.…”
Section: Discussionsupporting
confidence: 89%
“…Researchers cannot necessarily assume that translations of PROs from paper to electronic versions are equivalent [ 13 15 ]. The need to test measurement equivalence is determined by the level of modification required.…”
Section: Introductionmentioning
confidence: 99%
“… Immediate access to retrievable data [ 1 , 6 ] Potential to link ePRO data with electronic health records [ 6 , 12 , 13 ] Capacity to trigger automated alerts when patients identify problems [ 1 , 3 , 6 , 11 - 13 ] Immediate scoring and presentation of data [ 2 , 5 - 7 , 12 ] More economical in terms of resources and time [ 3 , 4 , 6 - 8 , 12 , 15 ] Greater likelihood of reporting sensitive information [ 1 , 2 , 5 ] Prevention of errors in data-entry [ 1 , 4 ] Observation of survey completion in real-time [ 1 , 5 , 6 , 11 ] Improved data quality [ 3 , 4 ] Less missing information [ 1 , 2 , 8 , 12 ] With minor modifications from paper to electronic formats, validation is not likely necessary [ 1 , 6 , 7 , 9 ] Patient satisfaction with electronic platform [ 1 , 2 , 5 , 7 , 11 , 14 ] Storage of longitudinal data [ 2 , 12 ] Web-based platforms allow reporting from multiple locations (ie home, clinic etc.) [ …”
Section: Introductionmentioning
confidence: 99%
“…With minor modifications from paper to electronic formats, validation is not likely necessary [ 1 , 6 , 7 , 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…Although patient selection was based on continence, a number of additional outcomes were compared to the video motion tracking data in order to assess whether there was a relation. These post‐operative outcomes included patient reported outcome measures (PROMs), lower urinary tract symptoms, measured using the International Prostate Symptom Score (IPSS), the lower urinary tract symptoms domain of the EORTC QLQ‐PR25 score (EORTC QLQ‐PR25 score), and post‐operative complications, which were registered in the patients' medical files as they occurred.…”
Section: Methodsmentioning
confidence: 99%